Contribuição à análise das taxas de cesarianas utilizando a classificação de Robson, a partir do estudo de mulheres com cesariana prévia, em um hospital universitário - Leonardo Magalhaes Ferraz (2015)
Introduction and Objectives: The increase in caesarean section (CS) rates is a global reality and has become a serious problem of public health. The World Health Organization (WHO) suggests that levels above 10-15% do not significantly reduce maternal and neonatal mortality. To evaluate CS rates, it is necessary to develop a classification system in order to identify which groups of pregnant women corresponds to the most common indications for CS, and investigate the reasons of this. The Robsons 10-group classification system allows a better analysis of practices and the development of means to reach acceptable CS rates. The classification divides pregnant women into ten groups based on obstetric characteristics at admission for delivery. The aim of this study was the analysis of group 5, composed of women with singleton term pregnancies, fetus in cephalic presentation, who had previous CS, and their CS rates. Another objective was to provide data to construct means to improve obstetric care in women with previous CS. Patients and Methods: Cross-sectional observational study that analyzed births in 2014 at the Otto Cirne Maternity of HC-UFMG in Belo Horizonte, with 2,118 pregnant women. Clinical data were collected in SISMater, an electronic information system, which automatically generates the 10 groups. Robsons group 5 (337 women) was selected and divided into subgroup 5A, composed of women with one previous CS and subgroup 5B, composed of women with two or more previous CS. Results: The overall CS rate was 36.4%, and group 5 was the largest contributor to this rate, with 13.0% of all indications. The CS rate in Group 5 was 81.9%. Most women had a high-risk pregnancy (51.0%), and 94.2% of high-risk pregnant women underwent CS (p <0.001). In subgroup 5A, CS rate was 76.2% and vaginal births rate, 23.8%. Most patients in this subgroup that underwent CS was admitted before spontaneous labor (72.0%). The majority of the pregnant women in subgroup 5A, admitted with gestational age below 41 weeks for CS, had a high-risk pregnancy (70.6%). The most frequent CS indication in subgroup 5A was the previous CS (75.7%). No significant differences were observed in maternal and neonatal complications in this subgroup when CS was compared with vaginal birth. Discussion and conclusions: CS rates in group 5 and, specifically, in subgroup 5A were high, according to the literature, since a significant proportion of these women were candidates for vaginal birth after CS (VBAC), on favorable terms. The subdivision of group 5 showed that vaginal delivery would be a safe option for patients with one previous CS, as there was no significant difference in the number of adverse outcomes compared with CS. One explanation for the high CS rate would be the large number of high-risk pregnancies, and, consequently, an earlier termination of pregnancy. However, 29.4% of cases in subgroup 5A had no obvious indication to anticipate the delivery. This suggests that some women underwent CS before it was necessary. Thus, Robson's classification is a useful tool for qualitative analysis of obstetric care with regard to the route of delivery.